A software tool for prediction of prosthesis failure at the carpometacarpal joint of the thumb. (May 2015) - Tandara, A. A.; Capeller, L. J.; Jarczok, M. N.; Mayrhofer, P.; Jung, M.; Daecke, W.
Early recognition of prosthesis failure is difficult. A tool that helps to identify faulty prosthesis – a cause of early implant loosening – is needed. The aim of this study was to detect early implant loosening by applying a software program EBRA (Ein-Bild-Röntgen-Analyse). EBRA was applied to the radiographs of a series of 76 patients, with a total of 102 thumb carpometacarpal joint de la Caffinière prostheses, with an average follow-up of 14.5 months (range 0.5–24). The data were used to draw graphs of cup migration and inclination over time. Corresponding regression lines of migration and inclination in relation to time were made up to the point of loosening. The gradient of regression was calculated for all implants. The gradient of regression on the x and y axes differed significantly between stable and loose implants. Loose and stable implants showed significantly different cup migration on the x and y axes over time. EBRA proved to be a reliable tool to visualize cup migration in the trapeziometacarpal joint and to predict implant failure.